2019
DOI: 10.21203/rs.2.15434/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Information needs and information seeking behaviour of people with dementia and their non-professional caregivers: a scoping review

Abstract: Background Patients with dementia often require full-time caregivers especially in the later stages of their condition. Patients and caregivers' access to reliable information on dementia is essential as it may have an important impact on patient care and quality of life. This study aims to provide an overview of the information needs and information seeking behaviour of dementia patients and their caregivers.Methods We conducted a scoping review of the literature and searched four electronic databases for eli… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(113 reference statements)
0
1
0
Order By: Relevance
“…He found that 27.0% of participants with internet access searched for information on cognitive disorders. In a review, Soong et al (2020) pointed out that persons with dementia and their caregivers often use the internet as a source of information concerning the disease, care provision, healthcare services and caregiver self‐care.…”
Section: Introductionmentioning
confidence: 99%
“…He found that 27.0% of participants with internet access searched for information on cognitive disorders. In a review, Soong et al (2020) pointed out that persons with dementia and their caregivers often use the internet as a source of information concerning the disease, care provision, healthcare services and caregiver self‐care.…”
Section: Introductionmentioning
confidence: 99%